The farnesoid X receptor agonist obeticholic acid upregulates biliary excretion of asymmetric dimethylarginine via MATE-1 during hepatic ischemia/reperfusion injury - Ferrigno, Andrea (PLoS One, 2018)
BACKGROUND: We previously showed that increased asymmetric dimethylarginine (ADMA) biliary excretion occurs during hepatic ischemia/reperfusion (I/R), prompting us to study the effects of the farnesoid X receptor (FXR) agonist obeticholic acid (OCA) on bile, serum and tissue levels of ADMA after I/R. MATERIAL AND METHODS: Male Wistar rats were orally administered 10mg/kg/day of OCA or vehicle for 5 days and were subjected to 60 min partial hepatic ischemia or sham-operated. After a 60 min reperfusion, serum, tissue and bile ADMA levels, liver mRNA and protein expression of ADMA transporters (CAT-1, CAT-2A, CAT-2B, OCT-1, MATE-1), and enzymes involved in ADMA synthesis (protein-arginine-N-methyltransferase-1, PRMT-1) and metabolism (dimethylarginine-dimethylaminohydrolase-1, DDAH-1) were measured. RESULTS: OCA administration induced a further increase in biliary ADMA levels both in sham and I/R groups, with no significant changes in hepatic ADMA content. A reduction in CAT-1, CAT-2A or CAT-2B transcripts was found in OCA-treated sham-operated rats compared with vehicle. Conversely, OCA administration did not change CAT-1, CAT-2A or CAT-2B expression, already reduced by I/R. However, a marked decrease in OCT-1 and increase in MATE-1 expression was observed. A similar trend occurred with protein expression. CONCLUSION: The reduced mRNA expression of hepatic CAT transporters suggests that the increase in serum ADMA levels is probably due to decreased liver uptake of ADMA from the systemic circulation. Conversely, the mechanism involved in further increasing biliary ADMA levels in sham and I/R groups treated with OCA appears to be MATE-1-dependent.